Remarks on Solutions of the Generalized Jackiw-Pi Model with Self-Dual Potential. Issue 1 (February 2020) - Huh, Hyungjin
Abstract : We derive the self-dual equations of the generalized Jackiw-Pi model with the self-dual potential (1.7). We also show that the finite energy solution of the generalized Jackiw-Pi model with special self-dual potential (1.9) satisfies the self-dual system which can be transformed into the Liouville type equation.